POTENSI TEGAKAN HUTAN ALAM SEKUNDER DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) UNIVERSITAS LAMBUNG MANGKURAT - Agus Tri Djayanto; Suyanto Suyanto; Mufidah Asyari (Universitas Lambung Mangkurat, 2022)
Secondary forest is the phase of forest growth from a bare site due to natural or anthropogenic causes to a climax again. One of the secondary forests in South Kalimantan is the Special Purpose Forest Area of Lambung Mangkurat University (KHDTK) which is located in Karang Intan District, Banjar Regency with an area of 1,617 ha. In the Bukit Mandiangin area there is a lot of secondary natural forest and even at that location there are springs that never dry up. However, until now there has been no recent data regarding the number and potential for the types of regeneration that grow in the secondary forest of the Mandiangin hill area. The purpose of this study was to obtain information about the potential for regeneration of secondary natural forests in the Bukit Mandiangin Forest Area with Special Purposes at Lambung Mangkurat University (KHDTK). The data collection technique was carried out by purposive sampling in accordance with land cover conditions, regional accessibility and time. The method used in this research is the plotted path method. Analysis of the data used is to use a formula by looking for Density and Relative Density, Frequency and Relative Frequency, potential per ha, calculate diameter and calculate tree volume. The potential for regeneration at the seedling level is 51,583 individuals/ha with the dominant species being mahan and incompressible. The dominant regeneration potential is based on the number of individuals at the pole level simultaneously with alaban and tengkook with a potential of 1,437 stems/ha.Hutan Sekunder merupakan fase pertumbuhan hutan dari dari keadaan tapak gundul karena alam ataupun antropogen sampai menjadi klimaks kembali. Salah asatu hutan sekunder yang ada di Kalimantan Selatan adalah Kawasan Hutan Dengan Tujuan Khusus Universitas Lambung Mangkurat (KHDTK) yang terletak di Kecamatan Karang Intan Kabupaten Banjar dengan luas mencapai 1.617 ha. Di Wilayah Bukit Mandiangin banyak terdapat hutan alam sekunder dan bahkan di lokasi tersebut terdapat sumber mata air yang tidak pernah kering. Meskipun demikian sampai saat ini belum ada data terbaru mengenai jumlah dan potensi untuk jenis-jenis permudaan yang tumbuh di Hutan sekunder Wilayah bukit mandiangin tersebut. Tujuan penelitian ini untuk memperoleh informasi tentang potensi permudaan hutan alam sekunder yang ada di Wilayah Bukit Mandiangin Kawasan Hutan Dengan Tujuan Khusus Universitas Lambung Mangkurat (KHDTK). Teknik pengambilan data dilakukan secara purposive sampling sesuai dengan kondisi tutupan lahan, aksebilitas wilayah dan waktu. Metode yang digunakan dalam penelitian ini adalah metode jalur berpetak. Analisis data yang digunakan adalah menggunakan rumus dengan mencari Kerapatan dan Kerapatan Relatif, Frekuensi dan Frekuensi Relatif, potensi per ha, menghitung diameter dan menghitung volume pohon. Potensi permudaan pada tingkat semai yaitu 51.583 indivdu/ha dengan jenis dominan adalah mahan dan mampat. Potensi permudaan yang dominan berdasarkan jumlah individu pada tingkat tiang secara beriritan alaban dan tengkook dengan potensi 1.437 batang/ha.